High-level Petri nets control modules for service-oriented devices: a case study - João Marco de Melo Pereira Mendes (2008)
- This paper describes a solution for the control ofservice-oriented devices based on modular and special adaptedHigh-Level Petri Nets process description of intra- and intercontrolactivities. The procedure is applied on a case studyscenario, corresponding to a real transfer system made of severalcontrol devices represented as service-oriented components ableto share information between them. The High-Level Petri Nets areadapted to associable models applicable to describe controlprocesses and sufficient elastic for different control strategies.Valuable and flexible control features are obtained from itsapplication, such as an integrated methodology for the modularcontrol with decision support and validation.